Fresh leaf yield and flowering responses of Brassica junceavarieties to varying nitrogen levels - Mabarani, Madhara Temba; Chitamba, James; Muziri, Tavagwisa (International Network for Natural Sciences, 2018)
An experiment was undertaken to evaluate fresh leaf yield and flowering responses of two Brassica juncea varieties (Paida and ZGS) to varying rates of nitrogen fertilizer ammonium nitrate (0; 100; 200 and 300 kg ha -1) during winter of 2007 under irrigation. The experiment was arranged as a 2×4 factorial treatment structure, laid in a randomized complete block design (RCBD) with three replications. Fresh leaf yield and days to 50% flowering were measured during the course of the experiment. There was significant difference (p<0.001) in fresh leaf yield of the varieties. Fresh leaf yield was significantly increased to 37.3 t ha -1 when 300 kg ha -1 of NH4NO3 was applied as compared to control plots (0 kg ha -1) which gave a yield of 32 t ha -1 . There was no significant difference (p>0.05) in days to 50% flowering due to different N treatments. There was significant difference (p<0.05) in days to 50% flowering of the two varieties, with Paida flowering 24 days later than the ZGS mustard. N level had significant effect only on fresh leaf yield whilst variety had significant effect on both fresh leaf yield and days to 50% flowering. The N rate of 300 kg NH4NO3 ha -1 was considered as the optimal dosage and Paida the best variety.